2013
DOI: 10.4236/jcdsa.2013.33a1005
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Planopilaris is a Common Scarring Alopecia among Iraqi Population

Abstract: Background: Scarring alopecia like discoid lupus erythematosus, lichenplanopilaris and scarring folliculitis are common skin problems where differentiations between them are often difficult in many cases. Objective: To report, study and evaluate cases of lichen planopilaris and characterize the different clinical points in favor of this disease. Patients and Methods: This case series descriptive study was done at Department of Dermatology-Baghdad Teaching Hospital from January 2010 to November 2012. Sixty seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Family history was negative in all patients and this is similar to what has been published [16]. The clinical picture of trichotillomania was not well elucidated in all previous reports but the present study for the first time had described well morphological patterns which might help in establishing the right diagnosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Family history was negative in all patients and this is similar to what has been published [16]. The clinical picture of trichotillomania was not well elucidated in all previous reports but the present study for the first time had described well morphological patterns which might help in establishing the right diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…In alopecia are at a usually there is a complete hair loss or there is early complete hair growth and there is nothing between, and exclamation mark hair are good helpful diagnostic sign in favor alopecia areata especially in the early active form. The only type of alopecia areata that could not be easily separated from trichotillomania is the moth eaten alopecia which is not un common variety of alopecia areata [16], in addition the presence of nail changes are more in favor of alopecia areata, and lastly patient with trichotillomania almost always had obsessive compulsive neurosis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with a previous report [15]. Also, the present study showed that LP was the second disease responsible for red gums, affecting two (20%) female patients, although LP is a common problem in the Iraqi population [16,17]. This finding is inconsistent with previously mentioned studies [11,13].…”
Section: Discussionsupporting
confidence: 63%
“…The fringe sign, as evident in 90% of patients in the present work, has diagnostic importance, as it is absent in other types of alopecia such trichotillomania, alopecia areata, and scarring alopecia like follicular lichen planus. [ 25 ] We postulate that the hair at the front and sides of scalp is short and uninvolved by stress of traction. Wearing a turban is increasingly being utilized by Iraqi females as part of a modern hairstyle or hijab, especially in the last 10 years, so we can anticipate more associated traction alopecia as has become evident in Turkish women.…”
Section: Discussionmentioning
confidence: 99%